3-Methoxy-5-methyl-12-phenylbenzacridinium Iodide - Malokhat Uktamova; Rintaro Koga; Fotima Mukhamedjonova; Tursunali Kholikov; Bakhtiyor Ibragimov; Kohei Torikai; Khamid Khodjaniyazov (Molbank, 2022)
N-alkylacridinium derivatives are some of the most popular azo dye templates. Herein, we report the synthesis of 3-methoxy-5-methyl-12-phenylbenzacridinium iodide (MMPBAI) via N-alkylation. The structure of MMPBAI was elucidated using 1H Nuclear magnetic resonance (NMR), 13C NMR, Electronspray ionization mass spectrometry (ESI-MS), and Fourier-transform infrared spectroscopy (FT-IR). MMPBAI could not visualize double-stranded DNA in agarose gel, although the structural core would still be interesting as a template for new azo dyes.